2014
DOI: 10.1016/j.jgar.2013.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Infections caused by fluoroquinolone-resistant Escherichia coli following transrectal ultrasound-guided biopsy of the prostate

Abstract: An increase in the number of infections with fluoroquinolone (FQ)-resistant Escherichia coli following transrectal ultrasound-guided biopsy of the prostate (TRUBP) was observed in Louis Stokes Cleveland Department of Veterans Affairs Medical Center. This study investigated whether these infections were caused by a single strain of E. coli possessing distinct resistance and virulence determinants. Of 15 patients with urinary tract infection, 5 were complicated with bacteraemia and 1 with prostate abscess. Thirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
3
7
0
Order By: Relevance
“…In this research, we observed two clones with 94.1% similarity and one clone with less than 85% similarity ( Figure 1 ). Our analysis of multi-locus sequence typing confirmed the presence of the pandemic B2-ST131 E. coli clone by the Achtman scheme in all ST43 isolates obtained by the Institute Pasteur scheme, in agreement with previous studies [ 5 ]. As such, it is important to maintain a surveillance system for the identification of clones representing a public health threat, particularly those that occur outside of the hospital environment.…”
supporting
confidence: 92%
“…In this research, we observed two clones with 94.1% similarity and one clone with less than 85% similarity ( Figure 1 ). Our analysis of multi-locus sequence typing confirmed the presence of the pandemic B2-ST131 E. coli clone by the Achtman scheme in all ST43 isolates obtained by the Institute Pasteur scheme, in agreement with previous studies [ 5 ]. As such, it is important to maintain a surveillance system for the identification of clones representing a public health threat, particularly those that occur outside of the hospital environment.…”
supporting
confidence: 92%
“…Along with multiple case reports, previous cross‐sectional studies have shown that 8–11% of patients presenting with PA had recently undergone prostate biopsies . In two such cases, PA was the result of infection with multidrug‐resistant Escherichia coli . As patients undergoing transrectal prostate biopsy are frequently given antimicrobial prophylaxis, it is important to be mindful of the rising emergence of multidrug resistance in post‐prostate biopsy infections …”
Section: Etiology and Natural Historymentioning
confidence: 99%
“…These patients, who are frequently older with coincident outlet obstruction, are at risk for PA from direct introduction of bacteria into the prostate. Along with multiple case reports, [21][22][23][24] previous cross-sectional studies have shown that 8-11% of patients presenting with PA had recently undergone prostate biopsies. 25,26 In two such cases, PA was the result of infection with multidrug-resistant Escherichia coli.…”
Section: Etiology and Natural Historymentioning
confidence: 99%
See 1 more Smart Citation
“…The 2016 FDA communication recommended that fluoroquinolones should not be used for patients with acute bacterial sinusitis, acute bacterial exacerbation of chronic bronchitis, and uncomplicated urinary tract infections unless no alternative treatment options were available [10]. We have previously reported increasing rates of fluoroquinolone resistance among Escherichia coli urinary tract isolates from our facility [1113]. Urologists and primary care providers were alerted to the problem of increasing fluoroquinolone resistance in 2010 due to an outbreak of infections with fluoroquinolone-resistant E. coli after transrectal ultrasound-guided prostate biopsy [1112].…”
Section: Discussionmentioning
confidence: 99%